Reading Attitude as a Mediator between Contextual Factors and Reading Behavior. Issue 1 (January 2015) - Lim, Hyo Jin; Bong, Mimi; Woo, Yeon-Kyoung
Background: Among the factors known to influence reading development and performance, attitude toward reading is shown to be particularly critical for developing learners. Reading attitude enhances independent reading, levels of engagement in classroom reading activities, and the amount and variety of topics in reading, which in turn influence reading skills and strategies. Reading attitude is an important element in students' active engagement and achievement in reading. Purpose: The first purpose of this study was to test whether Korean students' home literacy resources, parental support and parents' reading attitude, and teachers' use of instructional strategies in relation to reading could predict Korean students' reading attitude. The second purpose was to test a model linking family- and school-related factors, reading attitude, and reading behaviors and learning strategy use as outcomes. Specifically, we hypothesized that positive and negative attitudes toward reading would mediate the relationships between home, parent, and teacher variables and reading outcomes. Design: Using a nationally representative sample from the PISA 2009 database, we tested two structural equation models. Because there were two categories of outcomes examined in this study, we fitted the model separately for each outcome category. The first model (Reading Behavior Model) included reading activities such as reading for enjoyment, reading diversity, and online reading as outcome variables. The second model (Learning Strategy Model) shared the same model structure with the first one except that the outcome variables were use of learning strategies such as memorization, elaboration, and control. In both models, reading attitudes were hypothesized to mediate the relationship between contextual factors (i.e. gender, home resources, parental and teacher influences) and the reading/learning outcomes. Conclusions: Gender, books and other types of literacy resources in the home, and parents' attitudes toward reading functioned as consistent predictors of Korean students' positive and negative attitudes toward reading. Among the contextual factors, parents' reading attitude and parental support for reading directly as well as indirectly predicted students' reading behaviors via students' reading attitude. Parental support for reading and teachers' instruction and assignment strategies in reading directly predicted students' use of learning strategies as well. Positive attitudes toward reading also predicted students' use of memorization, elaboration, and control strategies. Thus, reading attitude was an important mediator between parent- and teacher-related contextual factors and reading/learning engagement of Korean adolescents.